A convenient synthesis of (E)-conjugated polyene sulfonyl derivatives with excellent stereospecificity. Issue 34 (22nd August 2018) - Yu, Chunyan; Lv, Zhongwen; Xu, Sheng; Zhang, Jun
Graphical abstract: Highlights: A highly selective synthesis of ( E )-conjugated polyene sulfonyl derivatives. The convenient protocol has a great generality. The reaction was manipulated under mild condition with high yield. Abstract: A highly selective synthesis of conjugated polyene sulfonyl derivatives is described via the elimination of disulfonyl chloride with readily accessible raw material dihaloalkane. The protocol offers a convenient way to form sulfonamides, sulfonates and even sulfones. Furthermore, this method was manipulated under mild condition with simple operation in high yield to afford only trans products.